The Effect of Application of The Auditory Intellectually Repetition (AIR) Cooperative Learning Model to Improve the Understanding of Mathematics Concepts - Hermawati, Eli; Pebriyanti, Indri; Fitriyani, Yani (International Conference on Elementary Education, 2021)
The problem in this research is that understanding of concepts in mathematics is still low. The objectives of this study were to describe the differences in understanding of mathematical concepts in the experimental class that received the AIR learning model and the control class who did not get the AIR learning model, to describe the differences in the increase in students' conceptual understanding between the experimental class that received the AIR learning model and the class controls that do not get the AIR learning model. This method uses the Quasi-Experimental method, while the research design uses the Nonequivalent Control Group Design. The dependent variable in this study is the understanding of the concept and the independent variable is the application of the AIR learning model. The subjects of this study were 25 students of class V A and 25 students of class V B, which amounted to 25 students at SD in Ciporang. The instrument used in this study was an essay test. The results showed that there were differences in the results after students were given conceptual understanding treatment using the AIR learning model. This is indicated by tvalue > ttable. Besides, the difference in increasing understanding of the concept can be shown by the results of the t-gain test, the results of tvalue > ttable. So that there are differences in the increase (gain) in understanding the concept of learning using the AIR learning model with those that do not use the AIR learning model.